Environmental justice and climate change : assessing Pope Benedict XVI's ecological vision for the Catholic Church in the United States (Lexington Books, 2013)
Environmental Justice and Climate Change: Assessing Pope Benedict XVI's Ecological Vision for the Catholic Church in the United States provides the most thorough theological treatment available on Benedict XVI's statements on human responsibility for addressing environmental degradation. Contributors include lay, ordained, and religious Catholic theologians, a philosopher, and bishops highlighting the contributions Pope Emeritus Benedict has made to Catholic teaching while offering fruitful directions for advancing concern about ongoing threats to the integrity of Earth.